Logatom articulation index evaluation of speech enhanced by blind source separation and single-channel noise reduction - Szymon DRGAS; Jędrzej KOCIŃSKI; Aleksander P. SĘK (Archives of Acoustics)
The subjective logatom articulation index of speech signals enhanced by means of various digital signal processing methods has been measured. To improve intelligibility, the convolutive blind source separation (BSS) algorithm by Parra and Spence [1] has been used in combination with classical denoising algorithms. The efficiency of these algorithms has been investigated for speech material recorded in two spatial configurations. It has been shown that the BSS algorithm can highly improve speech recognition. Moreover, a combination of the BSS with single-microphone denoising methods can additionally increase the logatom articulation index.